Emotional Competence Development in Graduate Education: The Differentiated Impact of a Self-Leadership Program Depending on Personality Traits - Montalvo-Garcia, Adolfo; Martí-Ripoll, Margarita; Gallifa, Josep (Frontiers in Psychology, 2021)
There is little research on the effectiveness of Self-Leadership Programs (SLP) in graduate education based on the progress in Emotional Competences Development (ECD), and only a few of the studies incorporate its relationship with the Personality Traits (PTs). This article studies the differentiated impact of an optional Self-Leadership Program (SLP), which has eight workshops with a learner-centered and experiential approach, depending on personality traits (PTs). With a quasi-experimental ex post facto design, students’ scores in EDC were analysed according to their PT extremes: introversion, antagonism, lack of direction, neuroticism, and closeness to experience. ANCOVA tests, with ECD pre-test as a co-variable, were applied for each PT. Results indicated that the SLP presented a differentiated impact in ECD in four of the five PTs: neuroticism, introversion, antagonism, and lack of direction. These findings can be a key element for the participating students in SLPs because self-leadership requires self-knowledge. ECD can contribute to more integral learning in the graduate education experience, enhancing the preparation for the world of work.